Superficial basal cell carcinoma treated with 70% trichloroacetic acid applied topically: a case study - Chiriac A; Brzezinski P; Moldovan C; Podoleanu C; Coros MF; Stolnicu S (Dove Medical Press, 2017)
Anca Chiriac,1–3 Piotr Brzezinski,4 Cosmin Moldovan,5 Cristian Podoleanu,6 Marius Florin Coros,7 Simona Stolnicu8 1Department of Dermatology, Nicolina Medical Center, Iasi, 2Department of Dermatology, Apollonia University, Iasi, 3Department of Dermatology, P. Poni Research Institute, Romanian Academy Iasi, Romania; 4Department of Dermatology, 6th Military Support Unit, Utska, Poland; 5Department of Histology, 6Department of Cardiology, 7Department of Surgery, 8Department of Pathology, University of Medicine and Pharmacy of Targu‑Mures, Targu-Mures, Romania Background: Basal cell carcinoma (BCC) is the most common form of skin cancer, affecting millions of people worldwide. The treatment concept for BCCs is the surgical one, but it is costly, as such, searching for alternative medical therapeutics is justified. Aim: To highlight the efficacy of high concentration (70%) trichloroacetic acid (TCA) as a choice therapy for low-risk BCC. Method and patient: Authors present, for the first time, the use of a high concentration TCA applied once a week for 2 consecutive weeks with a toothpick, on a patient with BCC on the right preauricular area. Results: On examination 4 weeks later, the lesion was not clinically and dermatoscopically evidenced. Conclusion: High concentration TCA could be an effective and safe, non-invasive choice of therapy for low-risk BCC, easy to perform, not expensive, with good cosmetic results, especially for patients who are not likely to undergo invasive or expensive treatments. Keywords: basal cell carcinoma, therapy, trichloroacetic acid, dermatology